Implementasi Hadis Relasi Guru dan Murid di STIBA Makassar: The Implementation of Hadith on Teacher-Student Relations at STIBA Makassar - Abdullah, Abdullah; Arifuddin Ahmad; Erwin Hafid (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2024)
This study examines the implementation of hadith concerning teacher-student relations within the context of Islamic education at STIBA Makassar. The focus of the research is on how the values embedded in the hadiths of Prophet Muhammad (PBUH) are applied in the interactions between lecturers and students on campus. The research employs a descriptive qualitative method with a hadith science and case study approach. Data were collected through observation, in-depth interviews, and document analysis. The findings reveal that teacher-student relations at STIBA Makassar are grounded in the principles of adab (proper etiquette), compassion, and respect, as taught in the hadiths. Character-building programs and the emotional closeness between lecturers and students are key examples of this hadith implementation. This research contributes to a deeper understanding of the significance of harmonious relationships in Islamic education and offers practical guidance for educational institutions on incorporating hadith values in academic interactions.